'E-banking' initiatives in Indian banks – a case of business process reengineering (BPR) implementation. (1st April 2011) - Datta, Saroj K.; Kundu, Sukanya
The intention of the paper is to find out whether e-banking initiatives in Indian public sector banks (PSBs) can be considered as a successful case of BPR implementation. Attempt has been made to study e-banking solutions adopted by Indian PSBs and to evaluate their performance in improving the level of customer satisfaction and the business performance of the PSBs. The study is based on secondary data on selected Indian public and private sector banks. The research shows that there is a growth in the usage of ATMs and in the volume of electronic funds transfer which reflects that customers prefer electronic delivery channel more than traditional branch banking. The growth of productivity indicators of reengineered banking process is higher than that of the partially computerised banks and banks following traditional mode of operation. The research work brings out that information technology (IT) application has a very prospective future in India.